Resveratrol Inhibits Hepatic Stellate Cell Activation via the Hippo Pathway - Chunxue Li; Rongrong Zhang; Yating Zhan; Jianjian Zheng (Mediators of Inflammation)
Liver fibrosis, which results from chronic liver injury due to factors such as chronic alcohol consumption, hepatitis virus infections, and immune attacks, is marked by excessive deposition of extracellular matrix (ECM). Resveratrol (Res), a polyphenol phytoalexin, has been demonstrated to show anti-inflammatory, antioxidative, antiproliferative, and chemopreventive activities. In recent years, Res has been found to inhibit liver fibrosis. Enhanced Hippo pathway activation has also been reported to inhibit tumor progression and liver fibrosis. In the present study, the role of the Hippo pathway in mediating the effects of Res on hepatic stellate cells (HSCs) was examined. We found that Res significantly suppresses HSC proliferation, reducing the cell index. Res induced HSC inactivation, reducing collagen deposition and α-smooth muscle actin (α-SMA) expression. In addition, Res contributed to HSC apoptosis, upregulating Bax and downregulating Bcl-2 expression. Notably, the Hippo pathway was involved in the Res-mediated suppression of HSC activation. Res enhanced the activation of the Hippo pathway and reduced yes-associated protein (YAP) and transcriptional coactivator with the PDZ-binding motif (TAZ) expression. Interestingly, the YAP overexpression inhibited Res-induced HSC inactivation and apoptosis. In conclusion, these results demonstrate that Res inhibits HSC activation, at least in part, via the Hippo pathway. The present study indicates a new antifibrotic mechanism of Res and provides novel insights into Hippo-mediated HSC apoptosis and HSC activation in liver fibrosis.